MiR‐708/LSD1 axis regulates the proliferation and invasion of breast cancer cells. (2nd February 2016) - Ma, Lin; Ma, Shan; Zhao, Guimei; Yang, Longqiu; Zhang, Peng; Yi, Qingting; Cheng, Shuguang
Abstract: Breast cancer is one of the most common malignant tumors in women worldwide. The microRNAs (miRNAs) are small, noncoding RNAs that regulate various biological processes, including breast cancer. miR‐708 played an important role in a variety of cancers. However, its involvement in breast cancer remains largely unclear. In this study, we found that forced the expression of miR‐708 in breast cancer cell lines decreased cell proliferation and invasion, whereas inhibition of miR‐708 increased cell growth and invasion. miR‐708 could directly target the LSD1 3′UTR to downregulate the expression. Further studies suggested that inhibition of LSD1 could phenocopied function of the miR‐708 overexpression in MDA‐MB‐231 cells .Overexpression of LSD1 could counteract the effects of miR‐708 on the proliferation and invasion. Taken together, the results indicate that miR‐708 may function as a tumor suppressor gene in breast cancer development, and miR‐708/LSD1 axis may be a therapeutic intervention in breast cancer in the future. Abstract : miR‐708 inhibited tumor cell proliferation and invasion. miR‐708 inhibited proliferation and invasion by inhibiting LSD1. miR‐708/LSD1 axis regulates the proliferation and invasion of breast cancer cells.